UNCOVERING THE MEANINGFULNESS OF INTERNATIONAL LEGAL INTERPRETATION: SOURCES, METHODS, AND EFFECTS - Maria Regina Sekar Kedaton Saputra (Problematika Hukum, 2020)
State-to-state relations are largely governed by international law, and how this legislation is interpreted affects how it is applied. The significance of international legal interpretation is examined in this article as a basis for fairness, stability, and collaboration among nations. Understanding and comprehending frequently complex international legal texts is a fundamental step in the difficult process of international legal interpretation. We go into great length in this article about the function of interpretation in international economic relations regulation, peacekeeping, state behavior regulation, global cooperation, human rights protection, and compliance promotion.Keywords: International law, Interpretation, function.